Motor cortex rTMS in chronic neuropathic pain: pain relief is associated with thermal sensory perception improvement. Issue 9 (25th January 2008) - Lefaucheur, J-P; Drouot, X; Ménard-Lefaucheur, I; Keravel, Y; Nguyen, J-P
Abstract : Background: Improvement in sensory detection thresholds was found to be associated with neuropathic pain relief produced by epidural motor cortex stimulation with surgically implanted electrodes. Objective: To determine the ability of repetitive transcranial magnetic stimulation (rTMS) of the motor cortex to produce similar sensory changes. Methods: In 46 patients with chronic neuropathic pain of various origins, first-perception thresholds for thermal (cold, warm) and mechanical (vibration, pressure) sensations were quantified in the painful zone and in the painless homologue contralateral territory, before and after rTMS of the motor cortex corresponding to the painful side. Ongoing pain level was also scored before and after rTMS. Three types of rTMS session, performed at 1 Hz or 10 Hz using an active coil, or at 10 Hz using a sham coil, were compared. The relationships between rTMS-induced changes in sensory thresholds and in pain scores were studied. Results: Subthreshold rTMS applied at 10 Hz significantly lowered pain scores and thermal sensory thresholds in the painful zone but did not lower mechanical sensory thresholds. Pain relief correlated with post-rTMS improvement of warm sensory thresholds in the painful zone. Conclusions: Thermal sensory relays are potentially dysfunctioning in chronic neuropathic pain secondary to sensitisation or deafferentation-induced disinhibition. By acting on these structures, motor cortex stimulation could relieve pain and concomitantly improve innocuous thermal sensory discrimination.